Effects of chemical combinations on the parthenogenetic activation of mouse oocytes - HAN, BAO-SHENG (D.A. Spandidos, 2013)
The aim of this study was to identify an optimal method for the parthenogenetic activation of mouse oocytes. Ethanol (EH), strontium chloride (SrCl(2)) and ionomycin calcium salt were each combined with cytochalasin B to induce the parthenogenetic activation of CD-1(®) mouse oocytes. Among the EH combination groups, the blastocyst formation and hatching rates of the group that was activated with EH and CB for 5 min were significantly higher compared with those of the groups that were activated for 7 and 10 min (P<0.05). Among the SrCl(2) combination groups, the blastocyst formation and hatching rates of the group that was activated with SrCl(2) and CB for 30 min were significantly higher compared with those of the groups that were activated for 1 and 2 h (P<0.05). Among the ionomycin calcium salt combination groups, the blastocyst formation and hatching rates of the group that was activated with ionomycin and CB for 3 min were higher compared with those of the groups that were activated for 5 and 7 min (P<0.05). Compared with the other two combinations, the experimental indicators of the EH combination groups were notably superior (P<0.05). For combined activation, simultaneous activation with two substances was significantly more effective than successive activation (P<0.05). For combined activation with EH and cytochalasin B in mouse oocytes, 5 min of parthenogenetic activation had significant advantages with regard to cleavage, blastocyst formation and blastocyst hatching rates. In addition, the activation rate of combined activation was higher than that of single activators. For combined activation, the simultaneous application of two activators has a superior effect.